2019
DOI: 10.1007/bf03652025
|View full text |Cite
|
Sign up to set email alerts
|

Student and teacher perspectives on spelling

Abstract: For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The findings of the present study suggest that many teachers in England over-rely on a limited range of strategies. This may also be linked to the reported lack of confidence amongst teachers (as suggested in Daffern & Critten, 2019), which reduces the application of a broader range of pedagogical approaches to teaching spelling in response to individual need. This is turn is further constrained by the guidance provided in the National Curriculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the present study suggest that many teachers in England over-rely on a limited range of strategies. This may also be linked to the reported lack of confidence amongst teachers (as suggested in Daffern & Critten, 2019), which reduces the application of a broader range of pedagogical approaches to teaching spelling in response to individual need. This is turn is further constrained by the guidance provided in the National Curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the majority of teachers reported themselves as being just moderately confident at teaching spelling, ways to better prepare them to teach spelling and an examination of the clarity of national guidance available should be considered. Daffern and Critten (2019) argue that the teaching of spelling in schools should focus on the development of instructional approaches to spelling that are consistent across schools. The finding that less than one-third of teachers in the present study reported having a spelling policy in their schools and over 50% reported devising their own resources is therefore notable in highlighting the impact of a lack of strategic direction of evidence-informed pedagogical approaches on the consistency of approaches and resources used by teachers.…”
Section: Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation